Ritual Function of Atik Talak Bala in Tanjung Bonai Aur Village, Sumpur Kudus Sub-District - Ramadhan, Prasety; Yurisman; Edi Satria (Kirana Publisher (KNPub), 2023)
This study discusses the Functions of the Atik Tulak Bala Ritual in the Tanjung Bonai Aur District, Sumpur Kudus District, Sijunjung Regency. The aim of this research is to find out how the Functions of the Tulak Bala Atik Ritual and how the implementation of the Tulak Bala Atik in the Tanjung Bonai Aur District. The theory used in this study namely Functionalism theory from Malinowski which explains about the function of the ritual. The method used is a qualitative research method with an ethnographic approach. The data collection techniques are field observations, interviews, and documentation. The findings from this study are that Atik Tulak Bala has a function as a way to resist evil things that are faced by society, as well as those that attack livestock or crops. Atik Tulak Bala also has a function as a way to eliminate conflicts that exist in society, because divisions that occur in society can be a disaster that will befall the nagari. Implementation of Atik Tulak Bala by walking from one end of the village to the other end of the village. The community really believes that the disaster that comes and affects the whole community, of course, must also be overcome by working together too. During the trip, participants are prohibited from participating in the halfway ritual, if they are unable to afford the participants may take the available vehicle, with the condition that they continue Atik until the last point of Atik, then Atik is closed by reading Du'a rejecting Bala and also praying for safety, so that all people are protected from disease outbreaks and their sustenance is facilitated. Finally, before the participants go home, they should rest first and eat together first.